Formulation of protein and DNA microparticulate vaccine systems - Brennan, Fiona S. (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2003)
This study involved investigation of protein and DNA-loaded microspheres manufactured with a range of polymers and under different manufacturing conditions. The polymers used during encapsulation were poly (lactide-co-glycolide) polymers with different ratios of lactic:glycolic acid. Microencapsulation was carried out using a modified double emulsion technique followed by either solvent evaporation or spray drying. Characterisation techniques used to examine the microspheres included scanning electron microscopy, particle size analysis, gel permeation chromatography, confocal microscopy, zeta potential measurement and differential scanning calorimerty. Release of protein or DNA from all batches was studied and fitted to appropriate mathematical models. Human Serum Albumin (HSA) was encapsulated in PLGA 75:25 and PLGA 50:50 following double emulsion formation and solvent evaporation. Spray-dried protein-loaded microspheres were also manufactured. Emulsification was carried out using either an Ultra Turrax (T25) or a Silverson mixer (L4R). Two emulsification times were used to study the effect of homogenisation time on the physicochemical properties of protein-loaded microspheres
Keywords: Pharmaceutics, Ph.D.; Ph.D. Trinity College Dublin